Peningkatan Kecerdasan Memori Spasial pada Anak Melalui Permainan Tradisional Engklek - Praditna, Ardi; Chivan Agustinus Siregar; Nafisya Ayu Evana; Herpan Syafii Harahap (Lombok Medical Journal, 2024)
Spatial intelligence, especially in a visual context, is the ability to construct, design, or arrange the structure of an object in space that includes various directions and positions. Spatial intelligence, especially spatial memory, develops throughout childhood along with the functional maturation of specific areas in the cerebral white matter tracts. Based on this, efforts to improve spatial intelligence are important to do in childhood, one of which is through the traditional game engklek. Children's spatial memory intelligence increases through the process of playing engklek. The engklek game can train the use of spatial memory through movement within spatial boundaries and cognitive mapping of the brain which represents images of the environment and objects in space. The method used in this literature review is by searching and reviewing various literature sourced from online databases such as PubMed as well, Google Scholar, and textbook.